Impact of parental rheumatoid arthritis on risk of autism spectrum disorders in offspring: A systematic review and meta-analysis - Sun, Cheuk-Kwan; Cheng, Yu-Shian; Chen, I-Wen; Chiu, Hsien-Jane; Chung, Weilun; Tzang, Ruu-Fen; Fan, Hsin-Yi; Lee, Chia-Wei; Hung, Kuo-Chuan (Frontiers in Medicine, 2022)
Background To investigate the association of risk of offspring autism spectrum disorder (ASD) with both maternal and paternal rheumatoid arthritis (RA). Methods The Embase, Medline, Cochrane Library databases were searched for studies that investigated the association of parental RA with risk of offspring ASD. The primary outcome was the associations of maternal/paternal RA with the risk of offspring ASD. Subgroup analyses were conducted based on the timing of maternal RA diagnosis (i.e., before/after childbirth) and geographical location (i.e., Western vs. Asian countries) of studies. Results Ten studies published between 2005 and 2022 involving 6,177,650 participants were analyzed. Pooled results revealed a significant association between maternal RA and the risk of ASD (OR = 1.246, p < 0.001, 10 studies), while there was no association of paternal RA with the risk of offspring ASD (OR = 1.104, p = 0.253, four studies). Subgroup analysis demonstrated no correlation between diagnosis of maternal RA before childbirth and the risk of offspring ASD (OR = 1.449, p = 0.192, four studies), while there was a significant association of maternal RA regardless of the timing of diagnosis with the risk of offspring ASD (OR = 1.227, p = 0.001, six studies). Subgroup analysis on geographical location showed a significant association of maternal RA with the risk of offspring ASD regardless of the study location (all p < 0.05). Conclusion Our findings supported an association between maternal RA and an elevated risk of ASD in offspring. However, given the limited numbers of studies investigating the risk of offspring ASD in mothers diagnosed with RA before childbirth, further studies are warranted to elucidate this issue. Systematic review registration [www.crd.york.ac.uk/prospero/], identifier [CRD42022358470].